KONFLIK KELAS DAN FENOMENA KOMUNISME DALAM HUBUNGAN STRUKTURAL MENURUT PANDANGAN KARL MARX - Syadzali, Ahmad (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2014)
Classconsciousnessis the important key wordin understanding Marxs thought. This phenomenonis actually theantithesisof theHegelianway ofthinkingthat is tooidealistic, which is thenreversedbyMarxin the context ofa moreempirical view. Hence theconcept ofcommunism is evolved by laterMarxs thought interpreters which become the extreme thinking against variousideologies, including religiousideology whichis in favor of thebourgeoisie.